Das selbstreflexive Ich-Subjekt als Angelpunkt rationaler Theologie bei Holm Tetens - Müller, Fabian (Array, 2019)
Holm Tetens, a philosopher from Berlin, reasons for the existence of God. In contrast to classical arguments for God’s existence, he uses a comparative way of reasoning. Tetens starts with naturalism, the prevalent metaphysics of present times, and tries to show that in comparison to that, theism is the more reasonable choice. Neither naturalism nor theism can be proven. Thus, Tetens has to find different criterion in other to show that theism is more reasonable than naturalism. In his understanding, a human being is a morally responsible I–subject (selbstreflexives Ich–Subjekt). Unlike naturalism, theism is compatible with this philosophical anthropology, making it the more reasonable metaphysic. This article aims to trace back Tetens argument and examines his claim that no metaphysic can pe proven by empirical data. A special emphasis is laid on Tetens’ concept of the morally responsible I–subject as the central criterion in order to choose between two metaphysics.